Increasing global literacy (GL) competence of university students to support the Indonesian International Student Mobility Awards (IISMA) program: Development of GL instructional framework - Sudarwati, Emy; Junining, Esti; Indhiarti, Tantri Refa (Universitas Islam Negeri Palangka Raya, Indonesia, 2024)
A preliminary study has found that Indonesian International Student Mobility Awards (IISMA) grantees faced a variety of challenges during their IISMA program at the destination universities. Therefore, this study aims to develop and implement a global literacy (GL) framework to help IISMA students improve their GL competence to survive during their stay in host universities. Ten IISMA awardees studying at one of the state universities in Malang, Indonesia, participated in this study. A qualitative mixed-method design was applied. The data were collected through FGDs, questionnaires, and in-depth interviews. Using a descriptive qualitative analysis, this study proposes a practical framework to aid IISMA students in improving their global literacy competence. The findings were in the form of an instructional framework that can be maximally applied by those who need to prepare students for the IISMA program. It is envisaged that this study can aid in developing GL competencies, enabling subsequent students to fulfill their responsibilities as change agents from a global viewpoint. The framework created in this study provides pedagogical implications for re-creating a subject-specific curriculum that incorporates student practice in GL. The study